PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PANDANREJO DAN DUSUN TEGALMIRI DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , KHAIRUL MUKHLIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Field practice aims to produce a final product in the form of a map. Measuring and mapping of a job that produces a spatial data information from the Earth's surface. Spatial data includes all the objects on the earth's surface, such as a high point and planimetric detail to be presented in the form of a map. This final project describes the measurement and mapping activities. The method is applied to the activity of making a control framework that maps measurement and horizontal control framework vertical control framework, detailed measurements and a high point, as well as depiction of a digital map. The results obtained in the measurement and mapping of the situation is a map scale of 1:500 on Hamlet Pandanrejo and Hamlet Tegalmiri, Banyuripan Village, Bayat District, Klaten Subdistric, Central Java Province. The results of the calculation of the linear accuracy of 1:78925 horizontal control framework of a given tolerance error of 1:7500 and the average closing control framework vertical height difference of 2 mm from the given tolerance of 11.198 mm, so measurement the map control framework has met specifications TOR. In the test results the map, to test planimetric by 80% and height by 60% with a tolerance given by 90% of the number of samples that have been tested, so that the map does not meet the test specifications of TOR and the quality of the resulting map is not good.